Pengaruh Jumlah Benih per Lubang Tanam dan Teknik Pemupukan terhadap Pertumbuhan dan Hasil Tanaman Kacang Tanah (Arachis hypogaea L.) - I Komang Kertayasa; Wawan Pembengo; Suyono Dude (Transbahasa, 2025)
Peanuts (Archis Hypogea L.) are one of the most important food sources, namely as a source of vegetable protein. This is because peanuts have high nutrition and are good for health, besides being good for health, peanuts also have a fairly high fatty acid content. This study aims to determine the effect of the number of seeds per planting hole on the growth and yield of peanut plants. This study was conducted in Boludawa Village, Suwawa District, Bonebolango Regency. The research method was carried out using a factorial randomized block design (RAK), the first factor was the number of seeds per hole (1 seed per hole, 2 seeds per hole) the second factor was the fertilization technique (tugal, larikan, sebar technique) with 3 replications and consisted of 6 treatments. Data analysis was carried out using ANOVA analysis of variance, where if the calculated f is greater than the f table, the smallest BNT test at 5% level will be carried out. The results of the study showed that the fertilization technique using the dip method had a significant effect on the growth and yield of peanut plants on plant height (4 MST), the fertilization technique using the spreading method had a significant effect on the growth and yield of peanut plants on the number of leaves (2 MST), and the weight of seeds per planting. The number of 1 seed per planting hole had a significant effect on the weight of seeds per planting.